Novel combination biologic therapy for recalcitrant psoriasis and psoriatic arthritis in a medically complex patient. (23rd November 2021) - Hanna, Sarah; Youssef, Peter; Lowe, Patricia
Abstract: For patients who do not achieve adequate disease control on biologic monotherapy, or monotherapy with an oral‐systemic agent such as methotrexate, combination biologic therapy may be considered. To the best of our knowledge, we report the first case assessing the safety and efficacy of the combination of an interleukin‐23 (IL‐23) inhibitor (risankizumab) with a tumour necrosis factor‐α (TNF‐α) inhibitor (golimumab) in the treatment of psoriasis and psoriatic arthritis. After twelve months of treatment with risankizumab and golimumab, our patient experienced a significant improvement in his psoriasis and psoriatic arthritis without any adverse effects to date.